Geoheritage assessment for the geoconservation and geotourism promotion of in the Altamira sector of the La Amistad International Park, Costa Rica - Mejía Agüero, Omar (2024)
In recent years, the study of geoheritage has gained global importance, and in the case of Costa Rica, the first investigations have been carried out to identify geosites, as well as the interest in establishing a geopark in the La Amistad-Pacífico Conservation Area. This research focuses on identifying, analyzing, and evaluating the geosites in the Altamira Sector of the La Amistad International Park (PILA, in Spanish) to understand their state of geoconservation and their potential for geotourism. The methodology consists of three steps: geosites identification through geomorphological mapping, fieldwork, and bibliographic research; historical-cultural characterization using documentation related to natural history, expeditions, art, and sacred sites; and geosites evaluation based on criteria such as form, condition, ecosystems, management, and conservation, as well as their relevance to geotourism and their impact on local communities. Four geosites were identified in the Altamira sector: Valley of Silencio, Kamuk Hill, Gemelo-Pittier Hills, and The Esperanza savanna. These geosites feature valleys dissected by channels due to fluvial processes, as well as landscapes shaped by steep volcanic slopes, river action, and periglacial processes. Historical-cultural references were found, including artistic documents, legends, and stories linking them to Costa Rican indigenous culture. Geosites evaluation revealed high scores in criteria related to intrinsic values that define these sites as highlights of geoheritage due to their unique characteristics. However, weaknesses were identified in the Use and Management criteria, primarily in terms of infrastructure to promote geotourism. It is concluded that the selected geosites are representative of their geological and geomorphological evolution, housing valuable information about the natural processes that shaped the territory and serving as evidence of the country's natural and cultural history. Additionally, they stand out as suitable places to promote geoheritage conservation through activities such as research, education, cultural events, and geotourism.